DOOR KITCHEN IN DKI JAKARTA - Simbung, Filip; Wowor, Wulanmeiaya (AGUSPATI Research Institute, 2024)
Looking at the high population growth from year to year, the need for food is increasing, so food processing services are a suitable concept for creating business opportunities in the food industry. DKI Jakarta is the right location to set up a food processing service business. Door Kitchen is a food processing service that comes with 3 different types of cuisine, namely Indonesian, Japanese and Chinese which can be ordered via the application. The purpose of this research is to carry out an in-depth analysis regarding food processing services that will be developed, so as to determine whether implementing this business is a viable option or not. The method used is primary data obtained through distributing questionnaires, observation and structured interviews. There were at least 115 respondents used as samples in this research. The research results reveal that the success of a digital-based food processing service business such as door kithcen can be influenced by market and marketing aspects, operational aspects, organizational and human resource aspects and financial aspects. Keywords: door kitchen, marketing aspect, operational aspect, organizational aspect, financial aspect